Мировая культура: Средневековье: энциклопедия / А. Порьяз; Худ. А. Акимов - Порьяз А. (Мировая культура, 2001)
Экземпляры: ч/з (ретро) / Инвентарный номер: 37042 / Цена: / Сис.шифр: 63.3(0)4 / Авт.знак: П 60 / ГРНТИ: 13.09 / ББК: 63.3(0)4-7 я7